Hannah's joy - Perry, Marta (New York : Berkley Books, 2012)
Years after leaving the Mennonite faith with her parents, the recently widowed Hannah Conroy returns to the simple life in Pleasant Valley with her toddler son to try and figure out where she truly belongs.
Includes an excerpt from Naomi's Christmas (p. [315]-320).
Keywords: Amish -- Fiction; Amish Country (Pa.) -- Fiction; Christian fiction; Love stories